2023
DOI: 10.1088/2051-672x/acdaaf
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of anodic coating process parameters of Al 5754 alloy by response surface method

Ilhan Celik,
Fatih Erdemir,
Isa Coruhlu

Abstract: Aluminum 5754 alloy appears as a candidate material for many engineering applications in terms of its lightness and strength values. The surface properties of this alloy need to be improved for applications where there is surface damage such as friction and wear. In this study, Central composite design was applied to investigate the influences of anodic coating process parameters (voltage, coating time and grit size) on the response (i.e. surface roughness and coating thickness). The competence of the mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Hence, it can be concluded that the results of single-factor experiments obtained in the study of multi-factor systems are often of little use for practical application. For the investigation of multi-factor systems, it is most appropriate to use statistical methods of experiment design, which make it possible to obtain models of multi-factor processes with a minimum number of runs [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be concluded that the results of single-factor experiments obtained in the study of multi-factor systems are often of little use for practical application. For the investigation of multi-factor systems, it is most appropriate to use statistical methods of experiment design, which make it possible to obtain models of multi-factor processes with a minimum number of runs [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%